A Rare Case of Chronic Primary Angle-Closure Glaucoma in a Young Woman with Coexisting Pathologic Myopia - Ni Putu Ayu Reza Dhiyantari; Nurwasis Nurwasis; Evelyn Komaratih; Yulia Primitasari (Department of Ophthalmology, Faculty of Medicine, Universitas Airlangga, 2021)
Introduction: Primary Angle-Closure Glaucoma (PACG) is usually present in adults older than forty and is more common in hyperopic eyes. Angle-closure is usually related to structural or developmental ocular abnormalities in young individuals. Case presentation: We presented a rare case of PACG in a 32 years old woman with pathologic myopia of -23.0 RLE. The chief complaint was blurring of the right eye three months before the visit. Right eye Intraocular Pressure (IOP) was 30mmHg-38mmHg despite treatment with three intra-ocular pressure-lowering agents. Axial length was 32.36 mm and 31.19 mm RLE. Anterior chamber depth was 2.36 mm and 2.60 mm RLE. Lens thickness was 5.07 mm and 5.40 mm RLE. Signs of GON and pathologic myopia were found in both eyes. GON was present asymmetrically (0.9 and 0.6 RLE), with the myopic crescent as well as baring and peripapillary atrophy. The optic disc was slightly tilted with the myopic crescent. There was also a marked sign of retinal pigment epithelium thinning and attenuation along with myopic chorioretinal atrophy. Conclusions: PACG in a young myopic individual is challenging to diagnose because myopia and glaucoma share similar optic nerve head pathology. Comprehensive examinations including gonioscopy, biometry, and OCT may confirm the diagnosis. In the presented case, angle-closure was caused by thick lenses and a shallow anterior chamber, along with excessively long axial length. Primary angle-closure at a young individual with myopic eyes is highly uncommon. Nonetheless, clinicians should always consider glaucoma even in the presence of high axial length and myopic fundus.